EDUKASI MEMBUAT MINUMAN SERBUK JAHE UNTUK MENINGKATKAN IMUNITAS PADA PERAWAT DALAM MENANGANI PASIEN COVID-19 - Remilda Armika Vianti; Nunung Hasanah (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
The hospital is a health service agency that focuses on curative efforts. Hospitals are required to have ideal resources to be able to provide the best service to patients. The Covid-19 pandemic that has hit the world is a tough challenge for health services. The increase in new cases is so fast that the graph of the improvement looks very sharp. Positive confirmed cases are also increasing while hospital resources are unable to accommodate the number of patients in the area due to limited isolation rooms and their facilities. RSUD Bendan Kota Pekalongan is a hospital designated by the government to become a line 2 (two) Covid-19 referral hospital. Various problems experienced by the hospital, including the limited number of isolation rooms, the limited number of PPE, the limited number of human resources for health workers. This results in various problems, one of which is the nurse's it can result in stress which results in decreased immunity. Therefore, education to give food supplement like ginger drink, especially nurses. Education is carried out by providing a pocket book on efforts to prevent Covid-19. After being given education services, there was a improvement for motivation and increasing imunity. Keywords: Covid-19, nurse, education, ginger drink